smu_1558c-mediated regulation of growth and biofilm formation in Streptococcus mutans - Zhou, Jing; Ma, Qizhao; Liang, Jingou; Pan, Yangyang; Chen, Yang; Yu, Shuxing; Liu, Yaqi; Zhang, Qiong; Li, Yuqing; Zou, Jing (Frontiers in Microbiology, 2025)
Streptococcus mutans is a key etiological agent in dental caries, owing to its strong ability to form biofilms through carbohydrate fermentation. Protein acetylation, facilitated by GNAT family acetyltransferases, plays a critical regulatory role in bacterial physiology, but its impact on S. mutans remains largely unexplored. In this study, we investigated the role of the GNAT family acetyltransferase encoded by smu_1558c in regulating the growth and biofilm formation of S. mutans. The deletion of smu_1558c resulted in impaired growth, reduced biofilm formation, and diminished synthesis of water-insoluble extracellular polysaccharides (EPS). Proteomic analysis revealed 166 differentially expressed proteins in the deletion mutant, with significant enrichment in pathways related to carbohydrate transport and metabolism, and translation. Notably, glucosyltransferases GtfB and GtfC, key enzymes in biofilm formation, were significantly downregulated in the deletion mutant, while ClpL, a Clp-like ATP-dependent protease involved in protein homeostasis under stress conditions, was highly upregulated. These findings highlight that acetyltransferase smu_1558c plays a crucial role in the growth, biofilm formation, and EPS synthesis of S. mutans through its regulation of carbohydrate transport and metabolism pathways, as well as stress response mechanisms. This study provides novel insights into the molecular mechanisms governing S. mutans pathogenicity and suggests potential therapeutic targets for caries prevention.